INDONESIA’S 2020 NEW PARADIGM OF COLLABORATIVE STRATEGIC OUTLOOK IN THE SOUTH-SOUTH COOPERATION (SSC) AS THE BRIDGE-BUILDER FOR THE POST-PANDEMIC DEVELOPMENT [PARADIGMA BARU PANDANGAN KOLABORASI STRATEGIS DI TAHUN 2020 MILIK INDONESIA DALAM KERJA SAMA SELATAN-SELATAN SEBAGAI UPAYA PENGHUBUNG PERKEMBANGAN PASCA PANDEMI] - Abraham Hino Samuel Jose (Universitas Pelita Harapan, 2020)
The role of middle-income countries and the LDCs have been empowered through the South-South Cooperation (SSC) since 1955 when the Asia-African Conference was held in Bandung, Indonesia. The SSC itself uses the frame of triangular cooperation to achieve sustainable development goals and technical collaboration with its member states. At the beginning of 2020, the annual press statement of Indonesia’s Foreign Minister speech emphasized Indonesia’s principle on diplomacy that mutual benefit within international cooperation needs to be done by reinforcing the new paradigm of multilateralism – a collaborative strategic outlook. This article linked the new paradigm with the current context of the world’s economic polarisation and its unprecedented impacts that has made shifts towards middle-income and least-developing countries to be more resilient and cooperative amid the pandemic. With the new landscape of the global economy, Indonesia is now challenged to move forward and reinforce its partnerships in multilateralism amidst the fading global altruism and protectionism, hence this was contested during the G-20 Sherpas meeting. The document-based and internet-based research with qualitative analysis in this article also considers the recent development of conferences and meetings with the stakeholders in SSC within the period of Mrs. Retno Marsudi’s term as Indonesia’s foreign minister from 2014 until 2020. The article concludes the trajectories of Indonesia’s post-pandemic public diplomacy in SSC, the new role of Indonesia as the bridgebuilder in the post-pandemic cooperation norms to achieve the SDGs through cooperation in the G-20, and public diplomacy for the political influence and economic interdependence. Bahasa Indonesia Abstract: Peran negara menengah dan terbelakang semakin diperkuat dengan adanya Kerjasama Selatan-Selatan (KSS) sejak 1955 ketika Konferensi Asia Afrika (KAA) diadakan di Bandung, Indonesia. KSS sendiri menggunakan kerangka kerjasama segitiga untuk mencapai agenda pembangunan berkelanjutan dan kolaborasi teknis bersama dengan negara anggotanya. Pada tahun 2020, Pernyataan Pers Tahunan Menteri Luar Negeri RI mempertegas prinsip diplomasi Indonesia bahwa keuntungan bersama perlu dicapai dengan memperkuat paradigma baru dalam multilateralisme yaitu pandangan strategis untuk berkolaborasi. Artikel ini menghubungkan paradigma baru tersebut dengan konteks polarisasi ekonomi dunia saat ini serta dampak yang sangat berpengaruh pada perubahan kepada negara menengah dan terbelakang untuk lebih tahan dan kooperatif ditengah pandemi. Dengan lanskap perekonomian dunia yang baru, Indonesia saat ini ditantang untuk maju dan memperkuat kemitraan dalam multilateralisme di tengah memudarnya altruisme global dan proteksionisme seperti yang telah diutarakan Indonesia pada pertemuan Sherpa G20. Penelitian di artikel ini menggunakan metode riset berbasis dokumen dan internet dengan analisa kualitatif yang mempertimbangkan rekam jejak mengenai perkembangan terbaru dari konferensi dan pertemuan dengan para pemangku kepentingan dalam kerangka kerja KSS selama masa jabatan Menteri Luar Negeri RI Ibu Retno Marsudi dari 2014 hingga 2020. Artikel ini menyimpulkan trayektori dari diplomasi publik post-pandemi Indonesia dalam KSS, peran baru dari Indonesia sebagai pembangun jembatan dalam norma kerjasama post-pandemi untuk mencapai agenda pembangunan berkelanjutan melalui kerjasama di G-20 dan diplomasi publik untuk pengaruh politik dan interdependensi ekonomi.